2010
DOI: 10.1159/000290041
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection without Immunomodulation Is Not Sufficient to Reduce First Relapse Severity in Experimental Autoimmune Encephalomyelitis

Abstract: Objectives: Multiple sclerosis can be characterized by a strong neuroinflammatory and progressive neurodegenerative component leading to prolonged disability. The synthetic compound R(+)WIN55,212-2 is reported to be neuroprotective at moderate doses and both neuroprotective and immunomodulatory at high doses, most likely due to differences in receptor affinities. In order to investigate the effects of neuroprotection and immunomodulation in an animal model of multiple sclerosis, we examined the impact of incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 120 publications
1
15
0
Order By: Relevance
“…Our previous experiments demonstrated that immunosuppressive cannabinoid doses reduced demyelination and axonal degeneration as well as improved clinical performance (Hasseldam & Johansen, 2010). Here, we further investigate the mechanisms involved in neuroprotection following low dose cannabinoid treatment in EAE.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our previous experiments demonstrated that immunosuppressive cannabinoid doses reduced demyelination and axonal degeneration as well as improved clinical performance (Hasseldam & Johansen, 2010). Here, we further investigate the mechanisms involved in neuroprotection following low dose cannabinoid treatment in EAE.…”
Section: Introductionmentioning
confidence: 86%
“…EAE was induced by immunization with 20 µg of the extracellular domain of rat Myelin Oligodendrocyte Glycoprotein (amino acids 1-125, MOG 1-125 ), as described previously (Hasseldam & Johansen, 2010). …”
Section: Disease Induction and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…These probably cause significant stress-responses that are known to be immunosuppressive in EAE (Bolton et al 1997). Importantly, there is no solid data to suggest that doses of medical cannabis cause significant immunosuppressive effects in MS, following analysis of peripheral immune responses (Killestein et al 2003;Katona et al 2005;Sexton et al 2014 (Pryce et al2003;Croxford et al 2008;Webb et al 2008;Hasseldam and Johansen 2010;Hernández-Torres et al 2014;BernalChico et al 2015). In EAE, this is seen by a better functional recovery and a reduced accumulation of disability following paralytic attack Baker et al 2011;Al-Izki et al 2014).…”
Section: Lack Of Marked Immunosuppressive Effects Of Cannabinoids In Eaementioning
confidence: 99%